Distributional impact of tax and welfare policies: Budget 2024 - Doorley, Karina; Duggan, Luke; Simon, Agathe; Tuda, Dora (ESRI, 2023)
In this Special Article we analyse the distributional impact of Budget 2024. Similar to last year, many reforms in this budget were temporary measures specifically aimed at combatting cost of living pressures. Compared to a baseline pegged to wage growth, we estimate that Budget 2024 will leave households across the income distribution better off, by 2.1 per cent of disposable income on average. The lowest income quintile of households experience the largest relative gain (5-6 per cent of disposable income) but the lowest cash gain (€13-€17 per week). Much of the income gain is driven by temporary measures, although there are above-wage-growth increases to many permanent parameters of the tax-benefit system too. We show that from 2020 to 2024, permanent changes to the tax and welfare system have resulted in small average income losses (-0.5 per cent of disposable income) compared to policy changes pegged to wage growth. We suggest that policymakers should move away from the use of temporary measures to compensate households for rising prices and should consider the adequacy of welfare payments to provide an appropriate standard of living at current market prices.
Keywords: Ireland